Ant responses in a lycaenid–ant symbiosis are not facilitated by cuticular compounds alone - Dany S. Zemeitat; Marianne Coquilleau; Naomi E. Pierce; Mark A. Elgar (Royal Society Open Science)
Initiating partnerships in protective symbioses can be asymmetrical if there is a risk of attack from their symbionts. Myrmecophiles may encounter chemically mediated recognition systems that allow the host ants to distinguish nestmates from natural enemies, including non-nestmate conspecifics. The immature stages of the lycaenid butterfly Jalmenus evagoras form an obligate symbiosis with workers of Iridomyrmex mayri that protect them against natural enemies. However, the first instar larvae cannot anticipate this colony-specific chemical recognition system, since they are unlikely to encounter workers from the same colony that tended their mother. We show experimentally that workers of I. mayri can use chemical signals alone to distinguish between conspecifics and the larvae of J. evagoras; between nestmate and non-nestmate conspecifics and between larvae tended by nestmate and non-nestmate conspecifics. Nevertheless, we also show experimentally that while workers paid more attention to fourth than second instar larvae, they did not respond more aggressively to larvae that had been tended by non-nestmate versus nestmate workers. These data suggest that workers pay attention to other signals, perhaps via tactile, visual or vibratory sensory modalities, thereby allowing the butterfly myrmecophiles to mitigate the risks associated with the chemically mediated colony-specific recognition systems of their ant hosts.